KAWASAN WISATA KULINER JALAN RODA (JAROD) SEBAGAI RUANG EKSPRESI WAKTU LUANG (LEISURE) MASYARAKAT KOTA MANADO - Awaluddin Hasrin; Abdul Rasyid Umaternate; Sangputri Sidik (Jurnal Community, 2020)
This paper aims to understand the practice of using leisure time in the Jalan Roda (Jarod) area of the city of Manado. This research is focused on coffee shops located in the culinary area of jalan roda in the city of Manado. The determination of this area by considering several aspects, namely the representation of coffee shops located in the city centers and the jalan roda area (Jarod) is a gathering point for all people in the city of Manado. Researchers used a qualitative descriptive analysis aimed at describing in depth the phenomenon of the existence of a culinary jalan roda in the city of Manado as a means or space for leisure expression for the people of Manado. Based on this research, jalan roda area (Jarod) the Manado City is a place where people can relax. This area is a gathering point for people from various backgrounds, ranging from students, brokers, artists, cultural figures, journalists, business people, and even public officials. Different from the concept of coffee, or modern coffee shops in general. Coffee shops in jalan roda (Jarod) is somewhat simpler. Far from modern impression. If in general the concept of modern coffee or coffee maker puts forward an attractive and instagramable interior design for the visitors. Jalan roda region (Jarod) actually retains it’s classic style. The table model is made lengthwise so that everyone who visits can sit at the table with other people who have not been known before.